2018
DOI: 10.1080/23744235.2018.1449962
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome

Abstract: Secondary SFTS acquired through human-to-human transmission leads to milder clinical representations and superior prognoses compared to primary SFTS, suggesting that the transmission route makes a difference in disease progression and clinical outcome of SFTS disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Veterinary doctors and co-workers have been infected with SFTSV through close contact with sick cats which were virologically confirmed to be infected with SFTSV. This indicates that there is a high risk of being infected with SFTSV from sick animals through direct contact, as is the case in human-to-human SFTSV infections [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Veterinary doctors and co-workers have been infected with SFTSV through close contact with sick cats which were virologically confirmed to be infected with SFTSV. This indicates that there is a high risk of being infected with SFTSV from sick animals through direct contact, as is the case in human-to-human SFTSV infections [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, precautions regarding direct contact and droplet transmission should be considered in both family members and HCWs [15]. Fortunately, most secondary patients show mild clinical presentations and good prognoses compared with the primary patient, suggesting that the transmission route makes a difference in SFTS progression [6].…”
Section: Discussionmentioning
confidence: 99%
“…SFTS is largely observed among farmers involved in agricultural activities as well as forest workers, and the majority of cases are reported in people of 50 years of age or older [2, 3]. Although SFTS is tick-borne disease, some studies have reported that SFTSV can be transmitted from person to person [46]. As this transmission is mostly driven by close contact to the index case, SFTS has been reported in healthcare workers (HCWs) [7], and asymptomatic infections have been noted in family members with close contact [4, 5].…”
mentioning
confidence: 99%
“…For people living in cities, they are less likely to be infected with SFTSV. And even human-to-human transmission, the greatest chance of occurrence was only the population who contact its blood, such as nurses or family members [53]. In addition, secondary SFTS infection leads to milder clinical manifestations compared with primary SFTS.…”
Section: The Effect Of Taking Interventionsmentioning
confidence: 99%